Attitudes towards advanced nursing roles in primary dementia care – Results of an observational study in Germany. (10th December 2020) - Michalowsky, Bernhard; Henning, Esther; Rädke, Anika; Dreier‐Wolfgramm, Adina; Altiner, Attila; Wollny, Anja; Drewelow, Eva; Kohlmann, Thomas; Biedenweg, Bianca; Buchholz, Maresa; Oppermann, Roman F.; Zorn, Daniela; et al.
Abstract: Aims: To demonstrate the attitudes of general practitioners (GPs), nurses, persons with dementia, and caregiver towards suitable tasks and qualification needs for and the acceptance and impact of advanced nursing roles in German dementia primary care. Design: Observational study using a questionnaire survey with 225 GPs, 232 nurses, 211 persons with dementia, and 197 caregivers, conducted between December 2017–August 2018. Methods: A questionnaire was generated that includes specific assessment, prescription, and monitoring tasks of advanced nursing roles in dementia primary care as well as qualification requirements for and the acceptance and the impact of advanced nursing roles. Data were analysed using descriptive statistics. Group differences were assessed using the Fisher's exact test. Results: Advanced nursing roles were highly appreciated across all groups. Assessment and monitoring tasks were rated as highly suitable, and prescription authorities as moderately suitable. Nurses felt less confident in assessment and monitoring, but more confident in prescribing as practitioners expected. Patients and caregivers would appreciate a takeover of tasks by nurses; nurses and practitioners preferred a delegation. A dementia‐specific qualification was rated as best suitable for advanced nursing roles, followed by 'no specific qualification' if medical tasks that only can be carried out by practitioners were delegated and an academic degree if tasks were substituted. Advanced nursing roles were rated as beneficial, strengthening the confidence in nursing care and improving the cooperation between professionals and the treatment. Practitioners assumed that advanced nursing roles would improve job satisfaction of nurses, which was not confirmed by nurses. Conclusion: There is an extended consensus towards the enlargement of advanced nursing roles, represented by high endorsement, acceptance, and willingness to reorganize tasks. Impact: Results debunk the common notion that German practitioners would be reluctant towards advanced nursing roles and a takeover of current practitioner tasks, supporting the implementation of advanced nursing roles in Germany. 摘要: 目的: 证明全科医师 (GP) 、护士、痴呆症患者和照料人员对德国痴呆症初级护理中高级护理角色的合适任务和资质需求、接受程度和影响的态度。 设计: 2017年12月至2018年8月期间, 采用问卷调查的方式, 对225名全科医师、232名护士、211名痴呆症患者和197名照料人员进行了观察性研究。 方法: 生成问卷调查表, 其内容包括痴呆症初级护理中高级护理角色的具体评价、处方和监测任务, 以及高级护理角色的资质要求、接受程度和影响。采用描述性统计进行数据分析。采用费希尔精确检验方式来评估组间差异。 结果: 所有群组均高度支持高级护理角色。评价和监测任务被评为高度合适, 且开处方权限被评为中等合适。在评价和监测方面, 护士缺乏信心, 但对医师所期望的处方工作更有信心。患者和照料人员对护士接管任务表示支持; 护士和执业医师更喜欢授权。对于高级护理角色, 特定于痴呆症的资格被评为最适合, 其次是'无特定资格' (如果医疗任务只能由执业医师执行, 则进行委托; 如果任务被替代, 则涉及学术学位) 。高级护理角色被评价为是有益的, 其增强了护理方面的信心, 提高了专业人员与治疗之间的协作。执业医师认为高级护理角色可以提高护士的工作满意度, 但这一点没有得到护士的证实。 结论: 我们对高级护理角色的扩大化有一个广泛共识, 这代表着我们对高级护理角色的高度认可、接受、以及重新安排任务的意愿。 影响: 研究结果推翻了德国执业医师不愿意从事高级护理角色和接管现有执业医师任务的普遍观念, 支持执行德国高级护理角色。